2004
DOI: 10.1381/096089204323093363
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease in Plasma Ghrelin Concentrations following Bariatric Surgery Depends on the Functional Integrity of the Fundus

Abstract: Fasting circulating ghrelin concentrations in patients undergoing diverse bariatric operations depend on the degree of dysfunctionality of the fundus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 36 publications
5
89
1
3
Order By: Relevance
“…With some knowledge regarding the possible mechanism of action of diversionary bariatric surgery some surgeons are targeting areas of Systematic review of fat-free mass loss TB Chaston et al hormonal importance, particularly ghrelin production. 62 Alterations in ghrelin levels are subject to the surgical technique with BPD, RYGB and more recently sleeve gastrectomy. Reduced postoperative levels of this important growth hormone secretagogue may result in excessive loss of FFM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With some knowledge regarding the possible mechanism of action of diversionary bariatric surgery some surgeons are targeting areas of Systematic review of fat-free mass loss TB Chaston et al hormonal importance, particularly ghrelin production. 62 Alterations in ghrelin levels are subject to the surgical technique with BPD, RYGB and more recently sleeve gastrectomy. Reduced postoperative levels of this important growth hormone secretagogue may result in excessive loss of FFM.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced postoperative levels of this important growth hormone secretagogue may result in excessive loss of FFM. 62,63 To date, quantitative definition of 'excessive loss of FFM' is lacking. An obvious way to set standards of %FFML is to use normative data to calculate appropriate fat and fat-free composition of weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Two further open studies 27,28 and a double-blind trial 29 extended this observation, but in the series of Garcia-Compean et al 27 no significant effects on body weight and gastric emptying were observed. As the fundus of the stomach is the main source of ghrelin 30 and has a sensory activity 31 regulating the total gastric capacity, we modified the technique described by Rollnik and included the fundus as a target area for BTX injection. Our results confirm the observation of Rollnik et al 26 and demonstrate, in a double-blind, placebocontrolled trial, that inhibition of the cholinomimetic synapses of the stomach in the antrum and fundus cause a reduction of the threshold of satiety in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Much is known regarding life with chronically reduced ghrelin levels because thousands of individuals have undergone Rouxen-Y gastric bypass surgery, which reduces ghrelin levels by 50-70% for weeks relative to weight-loss controls. Postsurgical ghrelin levels are even lower after total gastrectomy or sleeve gastrectomy (removal of the fundus) and remain so in the long-term (34)(35)(36)(37)(38)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). The Roux-en-Y gastric bypass and sleeve gastrectomy surgeries both produce massive weight reduction, greater than those of other surgical procedures that less effectively reduce ghrelin levels and improve the health of previously morbidly obese patients with low complication rates (37,78,79).…”
Section: Resultsmentioning
confidence: 99%